Reference publication year spectroscopy (RPYS) in practice: a software tutorial - Haunschild, Robin; Bornmann, Lutz (Scientometrics, 2022)
In course of the organization of Workshop III entitled “Cited References Analysis Using CRExplorer” at the International Conference of the International Society for Scientometrics and Informetrics (ISSI2021), we have prepared three reference publication year spectroscopy (RPYS) analyses: (i) papers published in Journal of Informetrics ; (ii) papers regarding the topic altmetrics; and (iii) papers published by Ludo Waltman (we selected this researcher because he received the Derek de Solla Price Memorial Medal during the ISSI2021 conference). The first RPYS analysis has been presented live at the workshop and the second and third RPYS analyses have been left to the participants for undertaking after the workshop. Here, we present the results for all three RPYS analyses. The three analyses have shown quite different seminal papers with a few overlaps. Many of the foundational papers in the field of scientometrics (e.g., distributions of publications and citations, citation network and co-citation analyses, and citation analysis with the aim of impact measurement and research evaluation) were retrieved as seminal papers of the papers published in Journal of Informetrics . Mainly papers with discussions of the deficiencies of citation-based impact measurements and comparisons between altmetrics and citations were retrieved as seminal papers of the topic altmetrics. The RPYS analysis of the paper set published by Ludo Waltman mainly retrieved papers about network analyses, citation relations, and citation impact measurement.